Analysis of human conflict with sumatran elephant (Elephas maximus sumatranus) in Peunaron East Aceh regency - Fahmy Armanda; Abdullah Abdullah; M Ali S (Jurnal Edubio Tropika, 2018)
Inger study aims analyzing human conflict with Sumatran elephants (Elephant maximus sumatranus) in Peunaron Sub-district, East Aceh Regency. Data collection was conducted from July to September 2016. The method used in this research is survey method and interview to the community in Peunaron Sub-district, East Aceh Regency. Interview conducted on 40 residents of Bukit Tiga, Peunaron Lama, Peunaron Baru, Arul Pinang, and 30 residents Lokop and surrounding areas. Data analysis by using multiple linear regression test using SPSS 16 software. The result of this research shows that (1) public knowledge about human conflict with Sumatran elephant with significance value 0,049 0,05. (2) Public perception of human conflict with Sumatran elephant, with significance value 0.000 0,05. (3) Community customs against human conflict with Sumatran elephant, with significance value 0.000 0,05. The conclusions in this study are (1) Knowledge, perception, and community habits affect the conflict between human and human elephant.Keywords: Analyzed, Conflict, Human, Sumatran Elephant and Community Perception.